Buddhist and Islamic Orders in Southern Asia : Comparative Perspectives - Feener, R. Michael; Blackburn, Anne M., 1967- (Book collections on Project MUSE., 2019)
This volume aims to foster interaction between scholars in the subfields of Islamic and Buddhist studies by increasing understanding of the circulation and localization of religious texts, institutional models, and ritual practices across Asia and beyond. Buddhist and Islamic Orders in Southern Asia scrutinizes religious orders (here referring to Sufi?ar?qas and Buddhist monastic and other ritual lineages) that enabled far-flung local communities to be recognized and engaged as part of a broader world of co-religionists, while presenting their traditions and human representatives as attractive and authoritative to new devotees. Contributors to the volume direct their attention toward analogous developments mutually illuminating for both fields of study, drawing readers' attention to the fact that networked persons were not always strongly institutionalized and often moved through Southern Asia and developed local bases without the oversight of complex corporate organizations.